Ecosystem elements in innovative pedagogy in Israel - BLAGORAZUMNAYA Olga (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
This article delves into the inventive strategies employed by Israel's education system to champion innovative pedagogy and how these strategies can lead to noteworthy advancements in the realm of teaching and learning. The authors emphasize the growing awareness of the necessity for forward-thinking approaches to education that can nurture creativity, critical thinking, and problem-solving abilities, preparing students to tackle the demands of the contemporary world. Israel has established itself as a global trailblazer in education innovation, largely due to its robust innovation ecosystem, rendering it an ideal subject for examining how innovative pedagogy can be cultivated through such an ecosystem. The Israeli Ministry of Education has introduced a variety of initiatives with the objective of promoting innovative pedagogy within schools. These initiatives encompass teacher professional development, funding for innovative projects, and the integration of digital technologies to enhance teaching and learning. Furthermore, research has demonstrated that the creation of an innovation ecosystem can wield a significant influence on the promotion of innovative pedagogy, leading to heightened student engagement, elevated academic accomplishments, and a greater sense of ownership in the learning process. The article concludes by advocating for teacher training in innovative pedagogies and a wider embrace of these educational approaches.